Gaze-dependent spatial updating of tactile targets in a localization task - Mueller, Stefanie; Fiehler, Katja (Frontiers in Psychology, 2014)
There is concurrent evidence that visual reach targets are represented with respect to gaze. For tactile reach targets, we previously showed that an effector movement leads to a shift from a gaze-independent to a gaze-dependent reference frame. Here we aimed to unravel the influence of effector movement (gaze shift) on the reference frame of tactile stimuli using a spatial localization task (yes/no paradigm). We assessed how gaze direction (fixation left/right) alters the perceived spatial location (point of subjective equality) of sequentially presented tactile standard and visual comparison stimuli while effector movement (gaze fixed/shifted) and stimulus order (vis-tac/tac-vis) were varied. In the fixed-gaze condition, subjects maintained gaze at the fixation site throughout the trial. In the shifted-gaze condition, they foveated the first stimulus, then made a saccade toward the fixation site where they held gaze while the second stimulus appeared. Only when an effector movement occurred after the encoding of the tactile stimulus (shifted-gaze, tac-vis), gaze similarly influenced the perceived location of the tactile and the visual stimulus. In contrast, when gaze was fixed or a gaze shift occurred before encoding of the tactile stimulus, gaze differentially affected the perceived spatial relation of the tactile and the visual stimulus suggesting gaze-dependent coding of only one of the two stimuli. Consistent with previous findings this implies that visual stimuli vary with gaze irrespective of whether gaze is fixed or shifted. However, a gaze-dependent representation of tactile stimuli seems to critically depend on an effector movement (gaze shift) after tactile encoding triggering spatial updating of tactile targets in a gaze-dependent reference frame. Together with our recent findings on tactile reaching, the present results imply similar underlying reference frames for tactile spatial perception and action.